Specificity of delictual legal relationship in case of poor-quality prenatal diagnostics services (civil, political, and legal aspects) - K.V. Egorov; E.S. Egorova (Ученые записки Казанского университета: Серия Гуманитарные науки)
This paper addresses the issues of the delictual (tort) liability for the poor-quality provision of prenatal diagnostics. The relevance of the research can be explained as follows: the issue of recovering the expenses for lifelong treatment and caring for a child born with the pathologies that had not been revealed by prenatal diagnosis of the child’s mother has been considered for the first time in Russian science. This problem is important not only for science and practice, but for every person who can face the birth of such a child. In the course of the research, the following main result has been obtained: it is possible to recover the expenses for lifelong treatment and caring for a child born with the pathologies that had not been revealed by prenatal diagnosis of the child’s mother. In addition, the analysis of the features of the conditions for the delictual liability for this kind of poor-quality medical service provision has allowed to identify the liability limits. The results of the research play a significant role for development of the Russian judicial practice. One of the conclusions is that there has been no a single claim for the recovery of the expenses for lifelong treatment and caring for a child born with the pathologies that had not been revealed by prenatal diagnosis of the child’s mother. At the same time, state benefits are often not enough to treat such a child and care properly for it. As a result, this paper opens the way for a new direction of judicial practice. This direction can offer new opportunities for children born with the pathologies that had not been revealed by prenatal diagnosis and for their parents.